Soybean crop intensification for sustainable aboveground-underground plant–soil interactions - Singh, Ramesh Kumar; Upadhyay, Pravin Kumar; Dhar, Shiva; Rajanna, G. A.; Singh, Vinod Kumar; Kumar, Rakesh; Singh, Rajiv Kumar; Babu, Subhash; Rathore, Sanjay Singh; Shekhawat, Kapila; Dass, Anchal; Kumar, Amit; et al. (Frontiers in Sustainable Food Systems, 2023)
The major challenges to grow soybean, other than unfavorable weather and small farm size, is non-availability of the quality inputs at the right time. Further, in soybean growing regions, crop productivity and soil environment have been deteriorated due to use of traditional varieties and conventional methods of production. Soybean crop intensification or system of crop intensification in soybean (SCI) is a method of agricultural production system that boosts the soybean yields, enhance soil environment and maximizes efficiency of input utilization, although contribution of SCI to crop productivity is not well understood since different genotypes of soybean exhibit different physiological responses. Therefore, a field study was conducted in 2014–15 and 2015–16 using three crop establishment methods [SCI at 45 cm × 45 cm row spacing, SCI at 30 cm × 30 cm, and conventional method at 45 cm × 10 cm] assisted in vertical strips with four genotypes [Pusa 9712, PS 1347, DS 12–13, and DS 12–5] in vertical strips using a strip-plot design with three replications. In comparison to standard methods of cultivation, adoption of SCI at 45 cm × 45 cm resulted in significantly higher stomatal conductance (0.211 mol H2O m-2 s-1), transpiration rate (7.8 mmol H2O m-2 s-1), and net photosynthetic rate (398 mol CO2 m-2 s-1). Implementation of SCI at 30 cm × 30 cm had significantly greater intercepted photosynthetic active radiation (PAR) (1249 mol m-2 s-1) than conventional method system, increasing crop by 9.6 to 13.3%, and biomass yields by 8.2 to 10.7%. In addition, under SCI at 30 cm × 30 cm, there were more nodules, significantly larger root volume and surface density, and increased NPK uptake over others. Significantly greater soil dehydrogenase activity, alkaline phosphatase activity, acetylene reducing assay, total polysaccharides, microbial biomass carbon and soil chlorophyll were found at 45 cm × 45 cm under SCI (13.63 g TPF g-1 soil hr-1, 93.2 g p-nitro phenol g-1 soil hr-1, 25.5 n moles ethylene g-1 soil hr-1, 443.7 mg kg-1 soil, 216.5 mg kg-1 soil, and 0.43 mg g-1 soil, respectively).